Análisis de la gestión del conocimiento emprendedor como parte del desarrollo de la formación vocacional emprendedora en un modelo de gestión del aprendizaje en incubadoras (LACCEI, 2024)
There are knowledge gaps regarding the transition from learning towards the sustainability of entrepreneurship projects, among them are the empirical exploration of the learning processes and the results involved in the potentiation of intrapersonal and interpersonal skills of entrepreneurs when they start your entrepreneurial project. The incubation process of a business idea in its preliminary stages allows us to understand the entrepreneur even more from individual perspectives, influencing behaviorally on it, and naturally with scope in the other stages of an incubator. Thus, the pre-incubation stage is critical and yet its study has been limited, increasing unsustainability in various ventures. Variables such as the intangible strategic resource, which can be used to develop a company's capacity and strategy, and in turn determine its position in the competitive market environment, have not been optimally developed. The purpose of this research is to analyze entrepreneurial knowledge management as a factor that affects the dimension of entrepreneurial vocational training, within the framework of a learning management model in incubators for entrepreneurs. For this, a probabilistic sample of enterprises in Colombia was selected, taking into account the size of microbusinesses from different sectors of the economy, in which the information is analyzed through statistical techniques of multivariate analysis. It is verified how the entrepreneurial knowledge management variable is determinant in a learning management model in incubators for entrepreneurs, in the sense that it allows the entrepreneur to take risks and take advantage of various situations in a positive way when starting a business.